External morphology of the immature stages of Runibia perspicua (Fabricius, 1798) (Hemiptera: Heteroptera: Pentatomidae) - Brandão, Marcela Nascimento; Brugnera, Ricardo; Grazia, Jocelia (Zootaxa, 2019)
The study of immature stages in Pentatomidae contributes to the knowledge in several areas, mainly systematics, ecology and agriculture. In faunistic inventories, nymphs comprise a significant part of the specimens collected, which often cannot be identified due to lack of knowledge about the immature. Here, we describe the external morphology of eggs and nymphal stages of Runibia perspicua (Fabricius, 1798). The egg is barrel-shaped with the surface of chorium covered by spines, forming polygonal markings interconnected by sheets, similar as observed in some species of Carpocorini. In all the nymphal instars the abdomen is characterized by having rounded reddish spots and an orange/yellow longitudinal macula in the middle of each abdominal tergite, from abdominal segment II to VII. The first instar is the most distinctive, standing out mainly by the head and thorax totally brown. From the second instar the head and thorax acquire pale color with irregular brown spots. The labium presents significant variations in size along the ontogenetic development showing a non-isometric pattern, when compared to the total length of the body. Illustrations and photographs of all the immature stages and the detailed morphology of some structures in SEM are provided.